2016
DOI: 10.1002/jhbp.408
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for latent distant organ metastasis detected by staging laparoscopy in patients with radiologically defined locally advanced pancreatic ductal adenocarcinoma

Abstract: Patients with large pancreas body-tail tumors and high CA 19-9 level are at greater risk for latent distant organ metastasis or PM, and should undergo staging laparoscopy routinely for accurate diagnosis (UMIN000023125).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
24
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 27 publications
5
24
0
1
Order By: Relevance
“…Regarding the tumor size and location, our results were consistent with previous studies (2,3,22,23). The larger the tumor, the more likely it is to have distant metastasis.…”
Section: Discussionsupporting
confidence: 91%
“…Regarding the tumor size and location, our results were consistent with previous studies (2,3,22,23). The larger the tumor, the more likely it is to have distant metastasis.…”
Section: Discussionsupporting
confidence: 91%
“…Our previous report also revealed an MST of 8 months in PDAC patients with peritoneal dissemination and 13 months in patients with locally advanced disease who had positive peritoneal washing cytology diagnosed by staging laparoscopy for radiographically defined locally advanced PDAC . Moreover, we also reported that pancreas body‐tail tumors and tumor size >42 mm in 110 patients with radiographically‐defined locally advanced PDAC were significantly risk factors for peritoneal metastasis . In this study, 65.4% of patients with pancreas body‐tail tumors >42 mm had peritoneal metastasis.…”
Section: Discussionsupporting
confidence: 68%
“…Moreover, the associated risk factors for OMD in presumed resectable PDAC patients are also under debate. Tumor size and increased carbohydrate antigen 19‐9 (CA 19‐9) values have been previously associated with OMD . Diagnostic laparoscopy is routinely utilized in certain institutions for the assessment of possible disseminated abdominal disease and prevention of unnecessary laparotomy .…”
Section: Introductionmentioning
confidence: 99%
“…Tumor size and increased carbohydrate antigen values have been previously associated with OMD. 5,[10][11][12][13] Diagnostic laparoscopy is routinely utilized in certain institutions for the assessment of possible disseminated abdominal disease and prevention of unnecessary laparotomy. 14,15 However, utilization of diagnostic laparoscopy in all patients is timeconsuming and costly, especially due to the limited sensitivity in identifying small metastases in the posterior liver surface and the visceral peritoneum of the small bowel.…”
Section: Introductionmentioning
confidence: 99%